A Holistic-Comprehensive Approach: Best Practices to Improve Health Policy for COVID-19 Pandemic - Setyawan, Febri Endra Budi; Lestari, Retno (Kesmas, 2020)
The COVID-19 pandemic affects entire communities and causes a huge impact on all life aspects which include biological, psychological, social, and spiritual well-being. Health systems and health policies are promising developments and opportunities to review progress and accelerate interventions in COVID-19 control. Studies devoted to core holistic-comprehensive issues surrounding this pandemic are limited. Therefore, this article aimed to review several best practice studies that reflect holistic-comprehensive approaches to COVID-19. A comprehensive literature review was written based on 15 articles from the data sources which are Google Scholar, Science Direct, ProQuest Health, and Medical Complete, and ProQuest Science Journals from 2010 to 2020, searched terms related to holistic, comprehensive, outbreak, pandemic, epidemics, and COVID-19. There are many evidence-based practices on safe and effective strategies to improve all aspects of well-being before, during, and after the COVID-19 pandemic. Among these promising strategies, a holistic-comprehensive approach could also be considered as a necessary action to improve health policy during the pandemic. A holistic-comprehensive approach involved providing bio-psycho-socio-spiritual care and offered a continuum of healthcare that provides promotive, preventive, curative, and rehabilitative services. A holistic-comprehensive approach to the COVID-19 pandemic requires a sustained commitment from entire communities, stakeholders, and policymakers to achieve better health outcomes for all.